NLO Response of Photoswitchable Azobenzene‐Based Materials. Issue 13 (11th July 2013) - Liaros, Nikolaos; Couris, Stelios; Maggini, Laura; De Leo, Federica; Cattaruzza, Fabrizio; Aurisicchio, Claudia; Bonifazi, Davide
Abstract The nonlinear optical (NLO) response of three π‐conjugated azobenzene (AB) derivatives was investigated under picosecond laser excitation by means of the Z‐scan technique to evaluate the effect of an ethynyl‐based conjugated spacer on the NLO properties of ABs. All modules possessed large third‐order nonlinearity, but unexpectedly it was the less extended AB derivative that exhibited the largest NLO response. This finding has been confirmed by means of DFT calculations and was attributed to a higher cis/trans ratio of the particular AB derivative in its investigated photoequilibrated state. Furthermore, the influence of the amount of cis isomer on the third‐order nonlinear susceptibility [χ(3)] of the less extended AB derivative has been thoroughly investigated. Specifically, modulation of the NLO response has been successfully achieved by tuning the isomeric composition of the investigated photostationary state. These results highlighted the cis‐dependent increase of the NLO response to support the general idea that such compounds can be used for multistep switching NLO materials.